Methods for rational strengthening of argumentation in the written discourse of human sciences (description and evaluation) - Savtchouk, Tatiana N. (Journal of the Belarusian State University. Philology, 2022)
The article presents the results of a descriptive and normative analysis of the problem of rationalising of humanitarian argumentative practice. Based on the material of Russian and Belarusian language texts published in peer-reviewed scientific journals, methods of intensifying rational influence in the written discourse of the humanities are identified and systematised. The means of rational strengthening of argumentation are differentiated at three levels of discourse analysis: structural, representational, and metatextual. It has been established that the methods of structural strengthening are: systematisation of presentation; the use of complex argumentative structures; the use of special methods of structuring the argumentation (repetition, gradation, period). It is shown that the representational strengthening of argumentation is carried out verbally and non-verbally. Verbal methods are the following: logical-semantic accentuation (linguistic marking of the constituents of argumentation, its forms, schemes, structures; logical accents using language intensifiers; introduction of means of intellectual assessment into discourse). Non-verbal intensification is carried out due to various forms of visualisation (tables, diagrams, graphs, drawings, photographs, etc.). It is noted that metatextual rationalisation occurs with the help of typographic means (font variation, underlining, different types of brackets, symbolic designations, vertical and horisontal spaces, etc.). The influencing effect of these techniques is explained by their ability to present systematically argumentative content, as well as to form a rational aesthetics of a scientific product that meets the expectations of the perceiving subject of written humanitarian discourse. It is emphasised that the conditions for the effectiveness of multi-level means of rationalisation are determined by their typological affiliation and that the objectivity of their critical analysis involves taking into account a wide context and situational factors. It is concluded that the cooperation of the author of the article and the editorial office of the scientific publication plays a significant role in enhancing the argumentative impact of a scientific publication.
Keywords: argumentation; rational impact; argumentative structure; argumentative verbaliser; written scientific communication; discourse of the humanities